2017
DOI: 10.1371/journal.pone.0172299
|View full text |Cite
|
Sign up to set email alerts
|

Distinct susceptibility and applicability of MDCK derivatives for influenza virus research

Abstract: Madin-Darby Canine Kidney (MDCK) cells are widely utilized as a substrate for influenza virus isolation and propagation due to the high yields of virus. Here we compared the conventional MDCK cell line, MDCK-SIAT1 and MDCK-London for viral production, cell survival, and suitability in testing antivirals using six influenza strains including two H1N1 (pandemic and epidemic strains), three H3N2 and one influenza B strain. Overall our results suggest that MDCK-London cell line is superior for virus culturing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…Presence of IAV from nasal swabs was assessed by isolation and propagation of the virus in Madin-Darby canine kidney (MDCK) cells with added trypsin according to standard protocol [ 25 ]. The choice of this technique was based on recent studies that showed that MDCK cell lines proved to be highly sensitive for IAV isolation [ 26 , 27 ]. Virus replication was confirmed based on the cytopathic effect (CPE) produced in the cells and also assessed by hemagglutination assay according to standard protocol [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Presence of IAV from nasal swabs was assessed by isolation and propagation of the virus in Madin-Darby canine kidney (MDCK) cells with added trypsin according to standard protocol [ 25 ]. The choice of this technique was based on recent studies that showed that MDCK cell lines proved to be highly sensitive for IAV isolation [ 26 , 27 ]. Virus replication was confirmed based on the cytopathic effect (CPE) produced in the cells and also assessed by hemagglutination assay according to standard protocol [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…MDCK cells modify cell-surface proteins with both α-2,6-linked and α-2,3-linked sialic acids (Ilyushina et al, 2012;Ito et al, 1997;Lin, Kappes, Chen, Lin, & Wang, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, entry efficiencies of Scotophilus bat CoV-512 and SARS-CoV in 11 different cells were evaluated using a lentivirus-based pseudovirus system. HEK-293T cells were selected as they have been used for the production of pseudoviruses; additionally, several cell lines were selected because they were used for the isolation and maintenance of viruses in other studies, such as Vero and PK15 cells for PEDV [17], MDCK cells for influenza viruses [18], and Fcwf-4 cells for FCoV [19]. Given that CoVs tend to replicate in the epithelial cells of enteric and respiratory tracts, Caco-2 and IEC-6 were selected.…”
Section: Discussionmentioning
confidence: 99%